'Telling our story... Creating our own history': caregivers' reasons for participating in an Australian longitudinal study of Indigenous children - Katherine Ann Thurber; Anna Olsen; Jill Guthrie; Rachael McCormick; Andrew Hunter; Roxanne Jones; Bobby Maher; Cathy Banwell; Rochelle Jones; Bianca Calabria; Raymond Lovett (BMC, 2018)
Abstract Background Improving the wellbeing of Indigenous populations is an international priority. Robust research conducted with Aboriginal and Torres Strait Islander peoples is key to developing programs and policies to improve health and wellbeing. This paper aims to quantify the extent of participation in a national longitudinal study of Aboriginal and Torres Strait Islander (Indigenous Australian) children, and to understand the reasons why caregivers participate in the study. Methods This mixed methods study uses data from Wave 6 of Footprints in Time, the Longitudinal Study of Indigenous Children. We conducted descriptive analysis of quantitative variables to characterise the sample and retention rates. We applied conventional content analysis to 160 caregivers' open-ended responses to the question, 'Why do you stay in the study?', identifying themes and overarching meta-themes. Results The study has maintained a high retention rate, with 70.4% (n = 1239/1671) of the baseline sample participating in the study's 6th wave. We identified seven themes related to why participants stay in the study: telling our story, community benefit, satisfaction, tracking Study Child's progress, study processes, receiving study gifts, and valuing what the study stands for. These related to two meta-themes: reciprocity, and trust and connection. Caregivers reported that participation was associated with benefits for their family and community as well as for the study. They identified specific features of the Footprints in Time study design that built and maintained trust and connection between participants and the study. Conclusions Our findings support the assertion that Aboriginal and Torres Strait Islander people want to be involved in research when it is done 'the right way'. Footprints in Time has successfully recruited and retained the current-largest cohort of Aboriginal and Torres Strait Islander children in Australia through the use of participatory research methodologies, suggesting effective study implementation and processes. Participants indicated ongoing commitment to the study resulting from perceptions of reciprocity and development of trust in the study. Footprints in Time can serve as a successful model of Aboriginal and Torres Strait Islander health research, to promote good research practice and provides lessons for research with other Indigenous populations.